Essentials of electromyography - Kamen, Gary; Gabriel, David A. 1961- (Human Kinetics, 2010)
The interest in and use of electromyography (EMG) have grown significantly in recent years. Researchers have found numerous clinical and research uses for EMG, including biofeedback, gait analysis, and clinical diagnosis for neuromuscular disorders. Yet, until now, few sources have been available to help novices understand the characteristics of the instrumentation, signal analysis techniques, and appropriate EMG applications. Essentials of Electromyography provides the perfect starting point for those who plan to use EMG because it aids in the comprehension of issues such as handling noise contamination to the area, slope, and variability of the EMG signal. The text is also a solid reference for practitioners who use EMG, including exercise scientists, physical therapists, occupational therapists, and motor development specialists. The book contains six detailed chapters discussing the anatomy and physiology of muscle, bioelectricity, EMG tools, signal processing, force-fatigue relations, and gait. Through Essentials of Electromyography, readers will learn both fundamental and advanced concepts regarding the principles of using EMG, including the use and abuse of electrical recordings of muscle potentials; discover the physiological basis of EMG signals, which is explained at an introductory level; and explore relevant topics such as electrode configuration, advanced signal processing theory, and locations for extracting EMG information. The text provides a solid review of the relationship between human anatomy and EMG as well as how EMG is applied to clinical areas. It showcases over 160 figures and many qualitative explanations to communicate the principles of EMG, the biophysical basis of EMG, and the appropriate applications of EMG. It also contains appendixes for readers with a deeper understanding of EMG and stronger backgrounds in math; those readers will have the opportunity to work through more detailed EMG calculations. The book is heavily referenced and illustrated with diagrams showing electrical circuits and the progression of electrical impulses. Essentials of Electromyography--which is also available as an e-book--will help readers learn how to apply EMG for biofeedback, back pain, sport activities, and other uses. The text pulls together information scattered in books and articles among the numerous disciplines that use EMG as a tool. With its clear presentation of the concepts and applications of EMG, Essentials of Electromyography will prove to be a valuable text for practitioners and students alike